Gd-doped ZnO-g-C3N4 nanocomposite: a novel photocatalyst for the photodegradation of eosin yellow dye in water - Charles Kwame Bandoh; Moro Haruna; David Adu-Poku; Bernice Yram Danu; Ophelia Pinto; Mandela Toku; Mercy Badu; Eric Selorm Agorku; Francis Kofi Ampong; Robert Kwame Nkum (Discover Applied Sciences)
Abstract The quest for effective and sustainable wastewater treatment technologies to remove impurities from our water sources has increased because of the recent rise in water pollution due to unprocessed industrial effluents discharged into our aquatic environment. Consequently, gadolinium-doped zinc oxide-graphitic carbon nitrite (Gd-ZnO-g-C3N4) heterostructures have been fabricated through the co-precipitation route in this study for the photodegradation of eosin Y (EY) dye in synthetic wastewater. Furthermore, the effects of different weight percent of Gd on structural and optical absorption properties, and photocatalytic behaviour of synthesized nanocomposites were studied. The structural, morphological, and optical absorption properties were confirmed through X-ray diffraction (XRD), Fourier transform infrared (FT-IR), and scanning electron microscopy (SEM) studies. A zeta potential study was also carried out using Dynamic light scattering (DLS) to determine the nanomaterials' surface charge and particle size distribution. The XRD analysis revealed a successful incorporation of Gd and g-C3N4 nanoparticles into the ZnO hexagonal crystal structure without any phase change. Optical absorption studies also showed a slight increase in absorption towards the visible region with an increase in Gd contents leading to a band gap shift from 3.10 to 2.90 eV. The introduction of Gd and g-C3N4 into ZnO nanoparticles enhaned the photoactivity of the pure ZnO with degradation efficiencies from 20% up to 96% and rate constants (k) from $$1.18{× 10}^{-3}$$ 1.18 × 10 - 3 up to $$19.23× {10}^{-3} {\text{min}}^{-1}$$ 19.23 × 10 - 3 min - 1 . The photocatalytic degradation of the dye followed the Langmuir–Hinshelwood model, with the reaction kinetics exhibiting a pseudo-first-order behaviour. The enhanced photoactivity of the nanocomposites was attributed to the combined effects of Gd and g-C3N4 in ZnO, which improved light absorption and charge carrier generation and separation. Graphical abstract